2020
DOI: 10.1021/acs.orglett.0c02442
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-Catalyzed Oxidative Phenol-Hydrazone [3+3] Cycloaddition Enables Rapid Construction of 1,3,4-Oxadiazines

Abstract: Herein, we present a hemin-catalyzed oxidative phenol-hydrazone [3+3] cycloaddition that accommodates a broad spectrum of N-arylhydrazones, a class of less exploited 1,3-dipoles due to their significant Lewis basicity and weak tendency to undergo 1,2-prototropy to form azomethine imines. It renders expedient assembly of diversely functionalized 1,3,4-oxadiazines with excellent atom and step economy. Preliminary mechanistic studies point to the involvement of a one-electron oxidation pathway, which likely diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In vitro , PM was associated with increased release of cytokines, such as IL-33, IL-1, IL-6, and IL-8 [ 25 27 ]. But in vivo , the relationship between PM and the release of associated cytokines remains uncertain [ 28 ]. Our study revealed that the airway inflammatory response aggravated by PM intervention was accompanied by elevated expression of IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , PM was associated with increased release of cytokines, such as IL-33, IL-1, IL-6, and IL-8 [ 25 27 ]. But in vivo , the relationship between PM and the release of associated cytokines remains uncertain [ 28 ]. Our study revealed that the airway inflammatory response aggravated by PM intervention was accompanied by elevated expression of IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, intermediate 279 is obtained from the silver-catalyzed cyclization of N'-( 2 In the same year, Wu and Zhong developed a mild, valuable strategy for synthesis of 1,3,4-oxadiazines 285 via hemin-catalyzed cycloaddition of phenol hydrazones [3 + 3] (Scheme 44). [77] This method is characterized by mild conditions, easy availability of all starting materials, good substrate universality, high yields, and excellent atomic and step economy. Obviously, a variety of hydrazones with different electron-withdrawing or electron-donating substituents can be used in this reaction to offer the desired products with moderate to excellent yields.…”
Section: Transition Metal-induced Cyclization Of Hydrazones With Unsaturated Systemsmentioning
confidence: 99%
“…Preliminary mechanistic studies pointed to the involvement of a one-electron oxidation pathway, which likely differed from the base-promoted aerobic oxidation scenario (Scheme 13). 93 Zhang et al developed the Pd(II)-catalyzed chemoselective intermolecular 1,2-oxyamination and 1,2-aminooxygenation of conjugated dienes 32 to afford 2-and 3-functionalized 1,4-benzoxazine derivatives 33 and 34, respectively. The reaction proceeded via the in situ generation of o-quinone monoimines from 31.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary mechanistic studies pointed to the involvement of a one-electron oxidation pathway, which likely differed from the base-promoted aerobic oxidation scenario (Scheme 13). 93…”
Section: Introductionmentioning
confidence: 99%